Impact of systolic pulmonary artery pressure on all-cause mortality in elderly cardiac patients. (4th March 2018) - Barywani, Salim Bary; Fu, Michael
Abstract: Objective. Elevated systolic pulmonary artery pressure (sPAP) is common among elderly patients with cardiac and pulmonary diseases. The lowest level of sPAP associated with increased mortality rate in octogenarians with cardiac diseases is however not sufficiently studied. Therefore, the present study aimed to identify the lowest level of sPAP associated with increased 5-year all-cause mortality in this patient group. Design. Of 538 octogenarians presented at the three Sahlgrenska University Hospitals (Sahlgrenska, Östra and Mölndal) with either congestive heart failure (CHF) or acute coronary syndrome (ACS), only 302 patients who had undergone echocardiography with data on sPAP were included in the present study. In order to identify the lowest level of sPAP associated with increased mortality rate, Cox proportional-hazard regression multivariable models were built for sPAP levels as low as 30 mmHg and upward with 5 mmHg intervals. Results . sPAP >35 mmHg was identified as the lowest level associated with increased 5-year all-cause mortality (HR = 1.7, 95% of CI = 1.1–2.6 and p = .013) . Every increase of 5 mmHg in sPAP was associated with a 10% increased relative risk for all-cause mortality. Conclusions . In octogenarians with cardiac diseases the lowest level of sPAP associated with increased all-cause mortality was >35 mmHg and the mortality rate increased with increasing sPAP.